An analysis of trends in Ph.D. research in tourism. Issue 1 (2nd January 2017) - Carr, Neil; Hayes, Stu
ABSTRACT: This paper provides an analysis of the research interests of Ph.D. students in the field of tourism. This type of assessment is important as it provides an indication of the research directions, health and diversity of the field. Examining the research interests of Ph.D. students arguably provided a window through which the current research foci of academic interest in tourism and potential future of research in the field can be viewed. The data set on which this paper is based was gathered from 1047 Ph.D. students who joined Trinet between mid-March 2007 and mid-July 2015. The data set was analysed using an abbreviated version of thematic analysis. The four mega-trends identified among the research interests of the Ph.D. students were: marketing, tourist behaviour, destination management, and sustainability. In concluding, the paper calls for academic research gatekeepers to maintain a balance between tourism 'management' and tourism 'studies' to ensure the vitality of the research field.